Laboratory Manual of Microbiology and Biotechnology - K R Aneja (Med Tech / Scientific International, 2014)
The intent of the manual is to provide basic and recent information and in depth methodology in a simple language about a wide spectrum of 144 exercises in a single tool essential for undergraduate and postgraduate courses in diverse areas of microbiology, biotechnology, biosciences, health-sciences, environmental science, agriculture, nutrition, pharmacy, medical laboratory technology, food processing units, and diagnostic laboratories. This clearly written, easy to use reference allows you to find what you need quickly. Unique features of this manual are: each exercise provides useful background information; an in-depth discussion of the principle involved; easy to follow the pattern of methodology with explanatory diagrams; expected results with interpretation profusely illustrated with coloured photographs to help students to perform practicals with their utmost ease in quest of achieving hundred per cent success; and the often asked questions at the time of viva-voce examination. This book is unique having experiments of multi-disciplinary nature and has a potential for a wide application. Unit I: Laboratory Safety Rules and Regulations Unit II: Principle and Working of Basic Equipment Unit III: Microscopy and Basic Microbiological Techniques Unit IV: Staining Techniques for Bacteria Unit V: Biochemical Tests Unit VI: Culture Media Preparation Unit VII: Basic Microbiological Techniques for Culturing Bacteria Unit VIII: Methods Used for Identifying Unknown Bacterial Isolates Unit IX: Study of Environmental Influences on Microbial Growth Unit X: Evaluation of Antimicrobial Agents Unit XI: Microbial Genetics and Molecular Techniques in Biotechnology Unit XII: The Fungi: Molds, Yeasts and Mushrooms Unit XIII: Parasitic Protozoa and Helminths Unit XIV: Virology Unit XV: Agricultural Microbiology Unit XVI: Environmental (Soil, Air, Water) Microbiology Unit XVII: Applied Microbiology and Biotechnology Unit XVIII: Medical Microbiology and Immunology